2020
DOI: 10.4085/1062-6050-181-18
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-Joint Self-Mobilization and CrossFit Training in Patients With Chronic Ankle Instability: A Randomized Controlled Trial

Abstract: Context Ankle-joint mobilization and neuromuscular and strength training have been deemed beneficial in the management of patients with chronic ankle instability (CAI). CrossFit training is a sport modality that involves these techniques. Objective To determine and compare the influence of adding self-mobilization of the ankle joint to CrossFit training versus CrossFit alone or no intervention in patients with CAI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the following two years, they would continue to suffer from symptoms such as decreased ankle range of movement, decreased muscle strength, proprioception abnormality, and decreased excitability of the nervous system, which weakened lower limb function and raised the risk of re-injury [ 57 , 58 ]. After the first injury, the recurrence rate is as high as 80% [ 54 ]. That is why the main purpose of the intervention is to increase the ankle range of movement, improve the nerve conduction capacity, enhance muscle strength and improve dynamic balance control.…”
Section: Discussionmentioning
confidence: 99%
“…In the following two years, they would continue to suffer from symptoms such as decreased ankle range of movement, decreased muscle strength, proprioception abnormality, and decreased excitability of the nervous system, which weakened lower limb function and raised the risk of re-injury [ 57 , 58 ]. After the first injury, the recurrence rate is as high as 80% [ 54 ]. That is why the main purpose of the intervention is to increase the ankle range of movement, improve the nerve conduction capacity, enhance muscle strength and improve dynamic balance control.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several trials examined the effects of the clinical use of MWM for rehabilitation in the case of ankle sprains but no study has thoroughly studied the therapeutic advantages. 9,10 Ho Jin Shin et al found that following an ankle sprain, the talus and distal part of the fibula was anteriorly displaced, the proximal part of the fibula was posteriorly displaced and the dorsiflexion range of motion (DFROM) was diminished in athletes with CAI, manual therapy at the joint of ankle, including mobilization and thrust-manipulation techniques has been proven to enhance pain relief, DFROM and dynamic balance whereas the specific manual therapy mechanism is difficult & unknown. 11 Shi X Han (2019) discovered that six sessions of manual therapy, rather than one improve the ankle functional performance in patients with CAI.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, SMR has become increasingly popular in fitness communities. CrossFit® athletes (CrossFit, Inc, Washingtion, DC, USA), for instance, regularly use SMR as part of their training routines to improve joint mobility [ 11 , 19 ]. Athletes are in control of the pressure, speed, frequency and other fine adjustments when performing SMR routines, which might account for their popularity.…”
Section: Introductionmentioning
confidence: 99%
“…SMR represents a simple and cost-effective conditioning approach, increasingly used as part of warm-up and post-workout recovery routines and, occasionally, embedded within training sessions [6][7][8][9]. Although physiological processes underlying the benefits of SMR remain poorly understood, SMR interventions have practical relevance in actual training contexts compared to static stretching [1,[10][11][12][13][14]. Pre-workout SMR interventions were associated with increased range of motion (ROM) without hindering forthcoming athletic performances such as jump height or performance across repeated sprints [15][16][17].…”
Section: Introductionmentioning
confidence: 99%